Anterior Ischemic Optic Neuropathy in a Child Receiving Chronic Hemodialysis. (16th March 2020) - Moore, Joyce; Klowak, Jennifer; Isaza, Gloria; Arora, Steven; Belostotsky, Vladimir; Stein, Nina; Chanchlani, Rahul
Abstract : Anterior ischemic optic neuropathy (AION) occurs due to hypoperfusion of the optic nerve and is a rare complication in patients receiving maintenance dialysis. To date, AION has only been reported in 22 children, all of whom were receiving peritoneal dialysis. We report the first case of AION in a 2-year 11-month-old child receiving chronic hemodialysis secondary to polycystic kidney disease from a phosphomannomutase 2 gene mutation. This case highlights the consideration for frequent blood pressure monitoring and ophthalmic screening in a certain cohort of children receiving chronic dialysis.